Methods, Developments, and Technological Innovations for Population Surveys. (August 2022) - Tomaselli, Venera; Battiato, Sebastiano; Ortis, Alessandro; Cantone, Giulio G.; Urso, Salvatore; Polosa, Riccardo
This article reviews contemporary issues in survey research, connecting established methods to innovative tools and technologies like real-time sensors and computer vision. This link takes into account the idea about the "organical" nature of Big Data, which represents a challenge toward a modernization of population studies in the light of technological innovations. The adopted dominant paradigm of data gathering is web survey (computer-assisted web interviewing), which is explored through the formalization of chain-referral methods as respondent-driven sampling. The general orientation is toward a computational social science approach. Weaknesses of such methodology is studied and solutions are provided with insights from empirical research on panel management. Contribution from gamification techniques is critically discussed.